The pathotype distribution of Puccinia recondita f. sp. tritici in India during 1987-89 - S. C. BHARDWAJ and L. R. VERMA, S.K. NAYAR, M. PRASHAR, J. KUMAR (Indian Phytopathology, 2002)
Pathotype 1048 (29R23) of Puccinia recondita f. sp. tritici, possessing virulence against Lr 23 was predominant followed by 77 (45R31) and 77-A (109R31) which match LrI3, LrI5 and LrI3, LrIO, Lrl5, respectively during 1987 and 1988 crop seasons. Pathotype 77 (45R31) predominated during 1988-89 followed by 77-A-I (109R23) virulent on LrIO, LrI3, LrI5 and 1048(29R23). Four new pathotypes, namely 12-3(49R37), 77-3(125R55) and 107-1(45R35) matching Lr26 and 108-1 (57R27) virulent on Lrl5 were identified during this period. Genes Lr9, LrI9, Lr24, Lr25, Lr28 & L;'29 continued to show resistance to leaf rust. Compared to 1983-86, effectiveness of Lr23 and Lr26 has reduced considerably during 1987-89.